Rediscovering Unexplored Hegelian Constellations for an Inclusive Bildung - Iannelli, Francesca; Achella, Stefania; Caramelli, Eleonora (B@belonline, 2024)
The article, and the research project described therein, aims to employ the methodology of the constellation research conceived by Dieter Henrich in order to shed light on the feminine contribution to Hegel’s life and philosophical path. Whereas studies on individual female poetic figures who have monopolized the attention of Hegel Scholarship in recent decades abound, there is a significant gap in the overall reconstruction of Hegel’s historical interaction with the women of his time. Beyond individual studies dedicated to Hegel’s wife Marie Helena Susanne von Tucher or the more controversial figure of his sister Christiane Luise, Hegelian constellations of the feminine have remained largely unexplored. Hence, exploring and rediscovering such constellations is not of circumscribable value as a merely biographical and corollary matter, but as a powerful magnifying glass that allows the appreciation of a number of qualifying aspects in the ethical, aesthetic and translational spheres, and which may reveal an emancipatory bearing of Hegel’s philosophy for contemporary debate.